Critical Discourse Analysis on Traveloka Hotel Review during the New Normal Era - Oka, Ida Bagus Made J. Radith; Laba, I Nengah; Utami, Gek Wulan N. (JAKADARA: JURNAL EKONOMIKA, BISNIS, DAN HUMANIORA, 2024)
This study aims to investigate the review of the hotel in Traveloka during the new normal. The objectives of the study are to explain the description dimension, interpretation dimension, and explanation dimensions of the review of the hotel in Traveloka. The study is analyzed using the Critical Discourse Analysis approach by Fairclough (1989). With a descriptive qualitative approach to obtain, gain, and explain the data. The findings emerged from this study: the description dimension showed the significant meaning of the word, active-passive sentences, and positive sentences were found in the review of the hotel, using description and persuasion structures. The interpretation dimension showed that the content, subject, relations, and connections were connected to the situational context. The explanation dimension in the situational context of praising and endorsing the resort is the main context of the review. The analysis discovered that hotel ratings are deeply connected with the larger social environment, the review referred to persuade the readers/guests with some praising and endorsing of the hotel, service, and amenities from the review the guest